Effectiveness of a Group Intervention Program for Female Victims of Intimate Partner Violence - Santos, Anita (2017)
Group intervention has been widely used with female victims of intimate partner violence (IPV). However, efficacy studies are scarce due to several research limitations. This study evaluates the effectiveness of an 8-week group intervention program, with a cognitive-behavioral orientation and attended by 23 female victims of IPV. Self-report psychological assessment was conducted at pre-test, post-test, and follow-up. Results revealed that the group intervention had a positive impact on participants, showing a decrease in re-victimization and in beliefs toward legitimizing IPV. A decrease in levels of depression and a significant improvement in general clinical symptoms were also evident. Self-esteem and social support were enhanced throughout group intervention. The changes were confirmed through follow-up after 3 months, suggesting that this group intervention has important effects on female victims. The implications of the findings for practice are also discussed.